Sistemas de proteção para redes de distribuição elétrica submarinas não aterradas - Barbosa, Diego Alexandre Belmonte (2017)
In the offshore world, the need for pumping expansion and subsea processing has been increasing in recent years mainly due to the search for optimization of resources and space in the platforms, in addition, a lot of cases, the subsea pumping is the only feasible of production projects. Thus, in order to achieve this, it is necessary to have the availability of power systems to meet this growing demand. In this way, this work aims to study the issues related to the protection system for a possible subsea distribution power system. For this system, an ungrounded distribution network is being considered, due to its advantages in the issues of not having large magnitudes of currents for ground faults. One of the issues to be studied in this work is the particularity of the use of power umbilicals for this submarine electrical distribution system. The use of power cable in ungrounded systems presents some challenges for earth faults as they lead to capacitive currents that contribute to faults in adjacent circuits. Such an effect ends up hampering the simple use of conventional overcurrent protections for radial distribution systems, leading to greater protection challenges. It is proposed in this work the modeling in the Matlab / Simulink software of the protection functions so that there is due reliability in the protection system for both threephase and single-phase faults from the platform exit to the terminals of the subsea frequency converters. A proposal for a protection system based on neutral directional functions using local or remote voltage measurements, or even without voltage tranformer, is presented. Simulation results are presented and analyzed and confirm their technical viability as an alternative to be applied in the subsea power system of the future.